Colour as a visual cue: how does package colour affect consumers’ perceptions? - Silva, Maria Margarida Bartolomeu (2017)
Visual stimuli play an important role in forming consumers’ perceptions regarding food products. Thus, the colour of packaging makes a significant contribution in promoting product sale and in influencing consumers’ buying desires and preferences. The purpose of this research is to try to fill the perceived gap in the existing literature in the field of food packaging and to enlighten the effects of colour on packaging. The present study used a quantitative approach to explain the link between colour combinations (complementary versus analogous colours) and consumers’ perceptions on calories, healthiness and purchase intention. Through a questionnaire, 383 respondents were asked to rate their perceptions on the variables mentioned, regarding two different packages for cookies: one coloured with blue and orange and another coloured with blue and green. The results demonstrated that blue and orange packages were perceived to be less healthy and more caloric, but participants revealed a higher intention to purchase them. Finally, managerial implications, limitations and future research directions are discussed.